Model Pembelajaran Kooperatif Team Game Tournament Berbasis Media Digital Blooket untuk Mengembangkan Motivasi dan Hasil Belajar Pendidikan Pancasila - Nani Nur’aeni; Erlangga Hanan Ilahiya Hasanudin (Asatiza, 2023)
Technology-based learning media has an important role in increasing learning motivation and student learning outcomes, one of which is web-based blooket media. Blooket media provides the pleasure of learning while providing learning challenges, activates student learning, and has relevance to the basic values of the independent learning curriculum. This research aims to determine the effect of the blooket media-based team game tournament (TGT) cooperative learning model. on motivation and learning outcomes of Pancasila Education. The research used a quasi-experimental design method with a research population of students at Cimanggung State High School and purposive sampling, the experimental class consisted of 31 people and the control class consisted of 31 people. Data analysis to assess learning outcomes uses paired sample t-test by providing learning outcomes tests in the form of pre-test and post-test, while learning motivation uses Likert scale analysis by providing a Motivation Questionnaire. The results of the research show that the TGT cooperative learning model based on digital blooket media has a higher influence on motivation and learning outcomes, compared to non-digital blooket TGT in Pancasila Education. The experimental class learning motivation interval score was 94% (very high) and the class interval score control was 54% (High) for experimental class learning outcomes was 77% (high) and for control class learning outcomes was 63% (Medium). with a t-test p-value <0.05 (0.000), indicating a significant effect.